Entrelaces de gerações: bisavós na família. - Schuler, Emily (2022)
The increase in human ageing is a phenomenon observed globally, bringing sociodemographic, cultural, and historical contexts that allow ageing and influence and enable the experience of various roles in the family. Consequently, more and more multigenerational families are emerging, formed by four or even five generations, therefore, more verticalised. The general objective of this research was to understand intergenerational relationships and their repercussions on the lives of great-grandparents and their families. Specifically, it aimed to: understand the sociodemographic context that allowed the development of the role of great-grandparents in Brazil; research about being great-grandparents in intergenerational relationships through a systematic review; understand the role of great-grandparents in the multigenerational family, and understand transgenerational transmission from greatgrandparents to their descendants. Therefore, this thesis was structured in two theoretical and two empirical articles. In the first article, a narrative review of the sociodemographic context that allowed the emergence of the role of great-grandparents in Brazil was carried out; the second article consists of a systematic review of the role of great-grandparents in intergenerational relations; followed by articles three and four that focus on the role of greatgrandparents and their transgenerational relationships. In the empirical articles, a qualitative methodology of multiple case studies with purposeful sampling was followed; the participants of this research were four families composed of four generations, totalling 16 participants. The inclusion criteria for great-grandparents were over 60 years of age and in a state of health that allowed them to participate in the research. The delimitation of the age of greatgrandparents was advantageous to understanding issues of the role linked to ageing. The participating great-grandparents (three great-grandmothers and one great-grandfather) were aged between 64 and 100 years old, their educational level ranged from illiterate to complete higher education, and most of them had widowed marital status, middle-low socioeconomic status and Christian religiosity. As for the other generations, whose inclusion criterion was availability to participate in the research, four children (46 to 66 years old), four grandchildren (26 to 40 years old) and four great-grandchildren (seven to 12 years old) were interviewed. A semi-structured interview was used with a specific script for each generation and a genogram in article three, and for article four, the triangulation of interviews with letters from great-grandparents to great-grandchildren and vice-versa. The interviews and letters were analysed according to the Thematic Content Analysis, and the Genogram was graphically analysed. The results indicate that the role of great-grandparents develops from family functioning and intergenerational relationships, bringing specificities to the role in each family. The role is intertwined with Intergenerationality, one of its primary functions being the transmission of legacies to the next generations. The transmission occurs mainly orally in the daily life of the family. Great-grandparents are seen as holders of wisdom in the Family and being someone who seems to influence the family directly. It was possible to observe that great-grandparents experience their role more lightly, seeking to enjoy their time and great-grandchildren. It is hoped that this research will contribute to the literature on greatgrandparents, which is still scarce in this country.